(untitled) (Global Journal of Human-Social Science, 2017)
In recent time the subject of media trial has been on the front burner of discussion among academics constitutional lawyers and judges Some of whom claimed the media is usurping the powers of the court in the administration of criminal justice while others have argued that the media are not at fault since they work with the information made available to them by the prosecutor To this end this study set out to investigate audience perception of EFCC media trials under the following specific purposes whether the EFCC engages in media trial the extent to which EFCC engage in media trial the effect of media trial on the public image of the accused and the impact of media trial on the anti-corruption campaign in Nigeria The study adopted the triangulation mixed method research design and measures the opinion of a sample of 399 respondents and 9 interviewees in selected local government areas in Enugu State through multi-stage sampling procedure The agenda setting theory served as the theoretical fulcrum upon which the data from the study was tested Findings from the study are discussed within the context of the much larger body of knowledge on media trial and the link with freedom of speech and fair trial